We all live here ebook A novel. - Moyes, Jojo (2025)
The #1 New York Times bestselling author, whose books so many love, brings us a fresh, contemporary story of a woman and her unruly blended family “Nobody writes women the way Jojo Moyes does.” —Jodi Picoult Lila Kennedy has a lot on her plate. A broken marriage, two wayward daughters, a house that is falling apart, and an elderly stepfather who seems to have quietly moved in. Her career is in freefall and her love life is . . . complicated. So when her real dad—a man she has barely seen since he ran off to Hollywood thirty-five years ago—suddenly appears on her doorstep, it feels like the final straw. But it turns out even the family you thought you could never forgive might have something to teach you: about love, and what it actually means to be family.